STRUKTUR DAN NILAI MORAL CERPEN "BARONGSAI MERAH PUTIH" KARYA ADE SUGENG WIGUNO - Yusep Ahmadi F; Eli Syarifah Aeni; Nurul Fauziah Marfuah (Jurnal Semantik, 2020)
This research is a research on the short story Barongsai Merah Putih by Ade Sugeng Wiguna. This short story was chosen because it is one of the short stories that entered the finalists of the Nusantara Writing Competition 2012. The formulation of this research is how the structure and moral value of the short story Barongsai Merah Putih. The method used is descriptive qualitative method. The data source was obtained from the short story Barongsai Merah Putih which was recorded with 9 other short story finalists published by Gramedia Pustaka Utama. The results of the study show that this short story has a complete set of intrinsic elements such as themes, characters and characterizations, settings / backgrounds, points of view, language style, plot, mandate. The moral values found are moral obedience, solidarity, perseverance, mutual cooperation, never giving up (persistence), and the value of patience. It can be concluded that the presence of intricate elements in the short story builds the short story to be coherent and rich in moral values.